Developing community-based forest enterprises in Nepal - Albano, A.; Pandit, B.H.; Kumar, C.; Belcher, B. (Center for International Forestry Research, 2008)
Developing community-based forest enterprises (CBFEs) is an ideal development intervention in poor forest communities as they have the potential to generate income and employment for the poor while supporting sustainable management of forest resources. This potential is limited by various constraints, many of which are unique to forestbased enterprises. In Nepal, there has been an increase in interest and efforts to develop forestbased enterprises following the institutionalization of various community-based forest management programmes; unfortunately, these initiatives are being impeded by several different factors. This policy brief summarises the important constraints affecting CBFEs in Nepal based from a study involving 28 different types of CBFEs. It identifies key areas for intervention and suggests specific developmental and regulatory interventions for the government and other key organisations involved in promoting CBFEs.